2013
DOI: 10.3390/ijms14011843
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bisindolylmethanes and Their Cytotoxicity Properties

Abstract: Polymer supported dichlorophosphate (PEG-OPOCl2) is an efficient green catalyst for the electrophilic substitution reaction of indole with aromatic aldehydes, in neat condition, to afford an excellent yield of bis(indolyl) methanes with short reaction time, at room temperature. The synthesized compounds and their anti-cancer activity are evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 35 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…In the 13 C NMR spectra of the products, the Ar–CH carbon signals were observed in the region of 54.1–32.2 ppm, confirming the formation of BIMs (Supporting Information). 37…”
Section: Resultsmentioning
confidence: 99%
“…In the 13 C NMR spectra of the products, the Ar–CH carbon signals were observed in the region of 54.1–32.2 ppm, confirming the formation of BIMs (Supporting Information). 37…”
Section: Resultsmentioning
confidence: 99%
“…We are interested in the development of various organic transformations under solvent-free conditions [20][21][22] and in exploring the catalytic properties of DBA in two different organic transformations. 15, 19 We found that DBA is a useful precursor for selective chemical transformations.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly bisindolylmethanes (BIMs) are widely existed in various natural products and exhibit a wide range of biological activities including anticancer activity against several cancer cell lines. 25,26 Bisindolylmethanes have been commonly prepared by reactions of indoles with various aldehydes or ketones in the presence of either Brønsted or Lewis acids. [27][28][29] Herein, the supported aza-crown ether complex cation ionic liquid containing [HSO 4 À ] was applied to the Friedel-Cras alkylation reaction as a good heterogenous catalyst.…”
Section: Introductionmentioning
confidence: 99%